MODERACIÓN DE NEUTRONES CON POLIETILENO Y PARAFINA - Aparicio O., Claudia (2004)
In this work it is presented the use of one solid state nuclear track detector, CR-39, for the determination of thermal neutron flux distribution from neutron sources, by means ofthe (n,p) nuclear reaction. Measurements of the thermal flux from an Am-Be neutron source with polyethylene and paraffin moderators were chemically etched in NaOH 6,25 N at 71 'C during 6 hours. An optical microscope 160X was used to observe the etched tracks. The flux profiles were obtained. 1t was found that polyethylene is a better moderator than paraffin for this neutron source.